Estudio del Patrimonio Material e Inmaterial en el Barrio Chan, Parroquia Eloy Alfaro, Cantón Latacunga, Provincia De Cotopaxi - Anchatuña Viracocha, Andrea Elizabeth (2018)
The main objective of this project is to prepare a descriptive guide through methods and techniques that allows the collection of information in order to contribute with the cultural heritage dissemination, it does not have a record of the Material and Intangible Cultural Heritage of the neighborhoods of Latacunga, one of them, Chan neighborhood, so the inhabitants are unaware of the cultural potential of the area and therefore do not consider important their registration, protection and dissemination, so the application of methodologies are proposed which allowed us to protect and disseminate the results among them the collection of primary and secondary information, selection and development of data collection instruments, questionnaires to identify key actors, application of interviews and field activities for the Inventory of Material and Intangible Cultural Heritage, the methodology of the Instituto Nacional de Patrimonio Cultural (INPC), through inventory cards. In the analysis and discussion of results a situational diagnosis of the place was determined, where the main stakeholders were the residents of the neighborhood, who contributed with primary and secondary information through interviews and as a result the current situation of the study area was obtained, it should be mentioned that it was analyzed in three main facts: Environmental-Geographical, Socio-Economic and Historical-Cultural. Within the results of the Material Cultural Heritage inventory, a total of 31 events were identified, where their state of conservation was 74% good, 19% with a regular conservation status and 7% were in a bad state of conservation. For the Inventory of Intangible Cultural Heritage a total of 31 events were obtained, with the following range of sensitivity to change, 54% had a high sensitivity to change, 26% average and 20% had low sensitivity to change